(3GdaYGdjI GdJfXjejI Hjf GdfXQjI h GdJWHjb (B:s (3age GdeHGOF ,Md GdeTcdGJ GdJfXjejI (B/s - (3JGhQjQjJ, fhQ GdOjf HTjQs ((3GQHO(B: s (3YGde GdcJH GdMOjK(B, s, 2009)
(3JWhQ GdacQ GdJfXjej h OQGSI GdefXeI , GdJYQja HGdGTcGdjI , GdJbjje GdJfXjej , GdaYGdjI GdJfXjejI , GdGWGQ GdELQGFj (B.s
(3eQGL U(B.245s
Keywords: (3GdEOGQIs; (3GdJNWjWs; (3JfXje hEOGQIs